2000
DOI: 10.1121/1.428426
|View full text |Cite
|
Sign up to set email alerts
|

Free localized vibrations of a semi-infinite cylindrical shell

Abstract: Free vibrations of a semi-infinite cylindrical shell, localized near the edge of the shell are investigated. The dynamic equations in the Kirchhoff-Love theory of shells are subjected to asymptotic analysis. Three types of localized vibrations, associated with bending, extensional, and super-low-frequency semi-membrane motions, are determined. A link between localized vibrations and Rayleigh-type bending and extensional waves, propagating along the edge, is established. Different boundary conditions on the edg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(60 citation statements)
references
References 7 publications
1
58
0
1
Order By: Relevance
“….. It is worth noting that at α ∼ β 1 2 all the terms in (3.11) are of the same asymptotic order as it is usually assumed in the dynamic semi-membrane theory [24].…”
Section: Dispersion Relationmentioning
confidence: 87%
See 1 more Smart Citation
“….. It is worth noting that at α ∼ β 1 2 all the terms in (3.11) are of the same asymptotic order as it is usually assumed in the dynamic semi-membrane theory [24].…”
Section: Dispersion Relationmentioning
confidence: 87%
“…see [1,24]. On introducing (5.1) into the Hamiltonian (2.2) taking into account formula (2.3) and integrating over the angle ϕ, we get by varying it in W an equation identical to (4.15) to within asymptotically secondary terms in α and β.…”
Section: Geometric Hypothesesmentioning
confidence: 99%
“…For this problem Kaplunov et al (2000) found an infinite discrete spectrum of edge-localized solutions, which are naturally related to the surface wave traveling along the strip edge. In her later work Wilde (2004) has also been able to use this spectrum in order to provide an empirical formulae for the edge vibration frequencies in the case of strip with free faces.…”
Section: Introductionmentioning
confidence: 99%
“…The result generalizes the edge wave which arises in the twodimensional approximate theory of plate extension (e.g. Kaplunov et al 2000).…”
Section: Explicit Solution For the Fundamental Edge Wave In The Case mentioning
confidence: 76%
“…Counterparts of bending and extensional edge waves also appear in the two-dimensional shell theory (e.g. Kaplunov et al 2000).…”
Section: Introductionmentioning
confidence: 99%